2015
DOI: 10.1038/srep10457
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the Aureobasidium pullulans-derived β-glucan effectively prevents the development of high fat diet-induced fatty liver in mice

Abstract: Aureobasidium pullulans-derived β-glucan (AP-PG) consisting of a β-(1,3)-linked glucose main chain and β-(1,6)-linked glucose branches is taken as a supplement to improve health. This study demonstrates that oral administration of AP-PG is effective to prevent the development of high-fat diet (HFD)-induced fatty liver in mice. Here, C57BL/6N mice were fed with a normal diet or HFD, and AP-PG diluted in drinking water was administered orally. After 16 weeks, the serological analysis showed that HFD-induced high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…β-glucan exhibits immune stimulatory activity, and is consumed as a supplement in many countries. Also, A. pullulans culture supernatant is believed to exhibit beneficial effects in delaying the onset of a number of diseases, and has been reported to exhibit antitumor, antiallergy and anti-infectious disease activities in mouse models [58][59][60][61][62][63][64][65][66][67][68]. An interesting review by Li et al [69] on Aureobasidium spp.…”
Section: Pullulan and Other Polysaccharidesmentioning
confidence: 99%
“…β-glucan exhibits immune stimulatory activity, and is consumed as a supplement in many countries. Also, A. pullulans culture supernatant is believed to exhibit beneficial effects in delaying the onset of a number of diseases, and has been reported to exhibit antitumor, antiallergy and anti-infectious disease activities in mouse models [58][59][60][61][62][63][64][65][66][67][68]. An interesting review by Li et al [69] on Aureobasidium spp.…”
Section: Pullulan and Other Polysaccharidesmentioning
confidence: 99%
“…Currently, an increasing number of studies have focused on polysaccharides extracted from different Chinese medicines due to their potential pharmacological activities. Many types of polysaccharides have shown appreciable effects in the amelioration of NAFLD or diabetes, such as Lycium barbarum polysaccharide 6 , Radix Hedysari polysaccharide 7 , Aureobasidium pullulans -derived β-glucan 8 , Rehmannia glutinosa polysaccharide 9 and Ganoderma lucidum polysaccharide 10 . Specifically, these polysaccharides have demonstrated hypolipidemic/hypoglycemic effects or antioxidative properties.…”
mentioning
confidence: 99%
“…It was reported that daily doses of 3 g of oat β‐glucan could help hypercholesterolemic people reduce plasma total and low‐density lipoprotein cholesterol levels (Othman et al., 2011). In line with this finding, Shiho Aoki et al noted that the Aureobasidium pullulans‐derived β‐glucan effectively prevented the development of fatty liver induced by a high‐fat diet in mice (Aoki et al, 2015). Based on this evidence, we hypothesized that β‐glucan may be an effective functional food for NASH treatment.…”
Section: Introductionmentioning
confidence: 78%